PENGEMBANGAN MODEL PEMBANGUNAN POLITIK DALAM PEMBENTUKAN MASYARAKAT MADANI : *MANIFESTASI MORALITAS KEKUASAAN - sobari, wawan (Jurnal Bestari, 2001)
The change of stategic environmental drives the teoritical study on development politic, include of civil society. Practically, it can be started via preliminary study consist of sysntesis and analysis the factual indonesia society now and the past and, after that, could be illustrated the formulae what kind the civil society in indonesia is? The beginner is not always the state, eventhought the state, should always, has great role to support, to facilitate and finalizing the civil siciety model in indonesia.